Screening and optimization of biosurfactant production by the hydrocarbon-degrading bacteria - Ainon Hamzah,; Noramiza Sabturani,; Shahidan Radiman, (Universiti Kebangsaan Malaysia, 2013)
Biosurfactants are amphiphilic compounds produced by microorganisms as secondary metabolite. The unique properties of biosurfactants make them possible to replace or to be added to synthetic surfactants which are mainly used in food, cosmetics and pharmaceutical industries and in environmental applications. In this study twenty hydrocarbon-degrading bacteria were screened for biosurfactant production. All of the bacterial isolates were grown in mineral salt medium (MSM) with addition of 1% (v/v) Tapis crude oil as carbon source. The presence of biosurfactant was determined by the drop-collapse test, microplate analysis, oil spreading technique, emulsification index (%EI24) and surface tension measurement. Only one isolate, Pseudomonas aeruginosa UKMP14T, was found to be positive for all the qualitative tests and reducing the surface tension of the medium to 49.5 dynes/cm with emulsification index of 25.29%. This isolate produced biosurfactant optimally at pH9.0 and incubation temperature of 37°C. Furthermore, P. aeruginosa UKMP14T when grown in MSM with addition of 1% (v/v) glycerol and 1.3 g/L ammonium sulphate with C/N ratio 14:1 produced biosurfactant with percentage of surface tension reduction at 55% or 30.6 dynes/cm with %EI24 of 43%. This percentage of surface tension reduction represents an increasing reduction in surface tension of medium by 39% over the value before optimization. This study showed that P. aeruginosa UKMP14T has the ability to biodegrade hydrocarbon and concurrently produce biosurfactant.